Potential yield and nutrient requirements of direct-seeded, dry-season rice in Cambodia - Kong, Kea; Hin, Sarith; Seng, Vang; Ismail, Abdelbagi M.; Vergara, Georgina; Choi, Il-Ryong; Ehara, Hiroshi; Kato, Yoichiro (Experimental agriculture, 2020)
The area of dry-season rice ( Oryza sativa L.) has rapidly increased in Cambodia owing to the large-scale development of irrigation infrastructure. But little is known of potential productivity and adaptive crop management. The objective of our study was to evaluate potential yield and nutrient requirements of dry-season rice in Cambodia, and the economic feasibility of soil-specific management recommended by the government. Field experiments were conducted on four soil types (Bakan, equivalent to Alfisol; Krakor, Inceptisol; Prateah Lang, Plinthustalfs; and Toul Samroung, Endoaqualfs) in four provinces (Battambang, Kampong Thom, Pursat, and Siem Reap) during the 2016 and 2017 dry seasons to compare 14 (2016) and 8 (2017) N-P-K combinations. Grain yield ranged from 1.0 to 5.5 t ha −1 in 2016 and from 1.3 to 6.7 t ha −1 in 2017. Potential yield from the experiments was 6–7 t ha −1 on Toul Samroung soil, 5–6 t ha −1 on Bakan soil, and 3–5 t ha −1 on Prateah Lang and Krakor soils. A rate of 140-60-60 kg ha −1 of N-P 2 O 5 -K 2 O was more than enough to achieve the best yields on any soil group. On the other hand, modest application rates in soil-specific management (44–78 kg ha −1 of N, 23–28 kg ha −1 of P 2 O 5 , 0–30 kg ha −1 of K 2 O) proved reasonable for resource-poor farmers in Cambodia, since the treatment always provided >75 % of the highest economic profit in high-input plots.